Pembagian Harta Bersama dalam Perceraian Tanpa Perjanjian Perkawinan dengan Istri sebagai Pencari Nafkah - Rina Auliana (AHKAM, 2026)
The division of marital property in marriages without a prenuptial agreement is often based on equal distribution, even when the wife serves as the primary breadwinner and bears most of the family’s economic burden. The absolute application of such equal distribution may disregard the parties’ actual contributions and result in substantive injustice. This study aims to analyze the juridical and sociological dynamics of marital property division for wives who serve as primary breadwinners and examine strategies for resolving such matters through notarial institutions. The study employed a normative-empirical juridical method by combining an analysis of positive legal norms, sociological facts in the field, and a jurisprudential approach. The results show that a formal approach oriented toward equal distribution often fails to consider the wife’s economic contribution proportionally. Therefore, marital property should be divided based on the principles of distributive and proportional justice, as reflected in the jurisprudence of the Supreme Court. Notarial institutions have a strategic role in facilitating out-of-court dispute resolution through a Deed of Marital Property Division Agreement. A proactive approach by notaries, an objective examination of documents and the origins of assets, and persuasive mediation can reconcile the interests of the parties and produce an authentic deed that reflects gender justice. This study affirms that the proportional division of marital property, supported by notarial instruments, can provide legal protection oriented toward substantive justice without compromising legal certainty.